A Qualitative Investigation of the Perceptions of Madrassa Students towards English Language - Dr. Aziz Ahmad (University of Chitral Journal of Linguistics and Literature, 2020)
The value of English language has been on the rise since the United States of America became the Superpower. English has become important and more like a Universal Language. In Pakistan too, it plays significant role in educational as well as professional circles. It is used as the official language in Pakistan. Among the various educational streams in Pakistan, one is Madrassa. Madrassas are religious seminaries; educational entities that impart religious education to students. The argument of this study is that these seminaries do not have effective teaching mechanism for English language teaching in their curriculum. This study intends to investigate the perceptions of students towards English Language, who had been to Madrassa or still going there as part-time students. The data is collected in the department of Islamic Studies, University of Malakand. Only enrolled students were included in the study. The number of respondents was ascertained from the departmental office and a total of 36 students were found qualified to participate in the study. The data was collected using interview method to investigate the views of the respondents about the importance of English language in educational and professional spheres. The significance of this study is that it highlights the need as well as reforms required in the curriculum. The study concluded that majority of students responded positively towards the need and value of English Language for madrassa students and implementation of practical policies in this regard.